Regulatory function of irradiated chitosan to antioxidant enzymes and growth of Capsicum annuum L - XU Chao; SHEN Kai; SHAO Luting; DING Xingcheng (浙江大学学报. 农业与生命科学版)
Chitosan can be used as the growth regulator to promote the germination, adjust crop growth, increase crop antioxidant enzyme activity and finally increase the crop yield and quality. However, due to the large molecular mass, chitosan would not be directly soluble in water and not easily absorbed by the plants, which restricts its application in agriculture. In all sorts of degradation methods, gamma ray irradiation is considered as an ideal polymer degradation method, because it has the characteristic of fast degradation speed, energy efficiency and almost no by-products.Capsicum annuum L. is a kind of favorite vegetables for people, but it cannot be stored for long time and difficult to transport. In order to improve the above mentioned properties of pepper, one method is to adjust the activity of antioxidant enzymes. It is reported in literature that chitosan has effects on the plant enzymes. However, whether the chitosan irradiated by 60Coγ rays also has effects on antioxidant enzymes was little known until now.The objective of the present study was to investigate the physiological responses of pepper to the irradiated chitosan, and to find the relationship between gamma ray dose and antioxidant enzyme activity. The obtained results would provide the scientific evidence for the application of irradiated chitosan in agriculture.The molecular mass of irradiated chitosan which was irradiated by different dose (0, 33, 66, 100 kGy) of 60 Co γrays was measured by the means of high performance gel permeation chromatography (HPGPC). Irradiated chitosan was dissolved to the concentration of 0, 50, 100, 200, 500 mg/L. The pepper seeds were soaked in the chitosan solution to investigate the germination rate. The pepper seedlings were transplanted to soil and planted. Chitosan solution was sprayed evenly on time. The activity of superoxide dismutase (SOD), peroxidase (POD) and phenylalanine ammonialyase (PAL) in pepper leaves and fruits was measured and analyzed by SAS 9.1. The mass of pepper fruits was also recorded.The results indicated that molecular mass of chitosan decreased with the increasing of ray dosage. The polydispersity index of all irradiated chitosan was nearly at 2.21, which was smaller than the value of unirradiated chitosan (2.63). The germination rate of pepper was restrained when the concentration of irradiated chitosan was less than 100 mg/L. At the condition of 66 kGy irradiation dose and the chitosan concentration of 200 mg/L, the germination rate was increased to 14.29% as compared to the control group. Both the irradiation dose and concentration of chitosan solution had significant effects on the activity of antioxidant enzymes in pepper. Enzyme activity gradually increased with the rise of irradiation doses, while the enzyme activity increased firstly and then decreased with the rise of the chitosan concentrations. The activities of SOD, POD and PAL increased by 43.17%, 55.56% and 60.00% than the control group, respectively, under the suitable condition. The mass of pepper fruits had the same tendency as the enzyme activity. The enzyme activity and fruit mass increased with the irradiation dose when the concentration of chitosan was less than 100 mg/L. While at the chitosan concentration of 100 mg/L, no matter what irradiation dose was, the enzyme activity and average mass of pepper fruit had the maximum values.In conclusion, the results suggest that: 1) The variation in pepper fruits mass results from the variation of enzyme activity in pepper plants caused by irradiated chitosan; 2) Irradiated chitosan can be applied as one of the motivating factor to changing the antioxidant enzymes activity, regulating the defense ability and finally adjusting the pepper growth; 3) High concentration of irradiated chitosan can inhibit the growth and metabolism of pepper fruits, which may contribute to extending the shelf life and quality of pepper.